Lumbrokinase-containing gelatin nanofibers with multiple bioactivities for effective skin wound healing - Wen-Ling Wang; Yi-Hui Lai; Chiung-Hua Huang; Jui-Yang Lai; Chun-Hsu Yao (Materials Today Bio)
Wound healing is a highly complex and intricate biological process involving cellular and molecular events. Given that lumbrokinase is a fibrinolytic enzyme derived from earthworms and exhibits notable anti-inflammatory, anti-fibrotic, and pro-angiogenic functions, this study aims to investigate the development of bioactive gelatin nanofibers containing lumbrokinase (GLK) fabricated through electrospinning as a novel nanomedicine strategy for enhancing wound healing. Our results showed that reducing electrospinning time can increase cross-linking degree and decrease degradation rate to maintain an effective concentration of released LK for supporting long-term biological processes. Cells cultured with biocompatible GLK displayed good adhesion and extensive spreading, increased VEGF production, and lowered IL-6 and TNF-α secretion. The GLK with superior and multiple bioactivities was further tested for tissue regeneration potential in a rat model of skin defect. The treatment of animals with GLK shortens wound healing time, reduces damage caused by inflammation, and increases collagen production, angiogenesis, and fibroblast proliferation/epithelialization, demonstrating that the healing effect on the local wounds is comparable to that of Comfeel group. Overall, the findings from preclinical studies suggest high promise of the LK-loaded biopolymer nanofibers as bioactive dressing materials for promoting a regenerative environment and accelerating wound healing, indicating its future translational potential.